USING CLOUD SERVICES TO CREATE THE EDUCATION AREA OF TEACHERS AND STUDENTS - Tiutiunnyk, Anastasiia V.; Honcharenko, Tetiana O. (Educological discourse, 2014)
The use of ICT in the learning process is considered as one of the most promising directions in improving the quality of education, individualization and personalization of the learning process. Article presents an analysis of the major integrated services, their opportunities for learning, describes the basics of Google services and the benefits of working with them in education. Made the survey functionality Google Apps for teachers and students and examples of their use. Presents opportunities to integrate Google Apps cloud services to e-learning courses Borys Grinchenko Kiev University.